A STUDY OF LEXICAL COHESION IN THE LYRIC OF DEMI LOVATO'S SONG IN 'TELL ME YOU LOVE ME' ALBUM - Moh Kavin Lidinillah (Fakultas Bahasa Asing (FBA) Universitas Mahasaraswati Denpasar, 2021)
The analysis of musical discourse analysis come from many ways and one of them is in song lyrics. Meanwhile, cohesion is a semantic relation which has a correlation between one component to another in the text. Lexical cohesion reached by selecting the vocabulary. There is one research problem in this study, what types of lexical cohesion are used in Demi Lovato’s song lyric in tell me you love me and the functions of Lexical Cohesion used. The study uses qualitative approach and uses Demi Lovato’s song lyric in tell me you love me. In conducting the study, the writers uses Halliday & Hasan (1976) theory of lexical cohesion which focuses on lexical reiteration (repetition, synonym/near-synonym, superordinate and general word). The result of the study shows types of lexical cohesion which is reiteration (repetition, synonym-near synonym, general word) only superordinates are missing. Therefore, the function of lexical cohesion in the lyrics of Demi Lovato’s song is to emphasize, to illustrate, to strengthen the message, and to give contribution to the two words that the meaning are connected to each other and make the song delivered clearly.